Understanding the impact of corporate branding on consumers’ emotional attachment towards premium smartphones in Malaysia - Neoh, Al Vin (2024)
In the global smartphone market, which generates $480 billion in 2023 and projected to grow 2.54% annually, Ultra-Premium smartphones priced above $1000 have claimed a significant market share, contributing to 21% of sales in 2022 with an impressive 94% year-on-year growth. The premium smartphone market faces heightened competition, with established players Apple and Samsung being challenged by cutthroat competition from Xiaomi, Oppo, and Vivo. For premium smartphone companies to sustain their growth in this competitive landscape, this research advocates for the strategic adoption of the Corporate Branding framework—a sophisticated, higher-level, corporate-wide organizational and marketing construct. However, a research gap exists regarding the degree of impact of Corporate Branding’s six components on consumer Brand Loyalty and Emotional Attachment. Drawing on a comprehensive study with 215 valid responses from Malaysian participants, utilizing a 7-point Likert Scale, the research reveals that Corporate Values, Corporate Personalities, and Functional Benefits positive influence Brand Loyalty, with these relationships being positively mediated by Emotional Attachment. Conversely, Corporate Associations, Corporate Activities, and Symbolic Benefits show no discernible impact on Brand Loyalty and are not mediated by Emotional Attachment. This study contributes significantly to the increasing recognition of consumer Brand Loyalty and Emotional Attachment as sustainable drivers of revenue growth, while offering strategic insights relevant to major smartphone industry players aiming to strengthen their market share.